Refracture Rate of Both Bone Forearm Fractures: A Retrospective Comparison of Casting Alone Versus Casting and Extended Functional Bracing. Issue 5 (12th May 2021) - Soumekh, Lisa; Sylvanus, Tonye; Karlen, Aaron; Wahl, Caitlin; Huser, Aaron J.; Truong, Walter H.
Abstract : Background: One of the most common pediatric fractures is a midshaft both bone forearm fracture. The preferred nonoperative treatment is cast immobilization for 6 to 8 weeks; however, 4% to 8% refracture within 6 months. There are no comparative studies evaluating the efficacy of bracing after cast immobilization. We hypothesized that children treated with prolonged functional bracing would have a lower rate of refracture than casting alone or short-term bracing. Methods: This is a retrospective review of children younger than 15 years of age treated nonoperatively following radius and ulnar shaft fractures treated at 3 tertiary pediatric hospitals. We excluded distal radius/ulna fractures, isolated fractures of the radius/ulna, and fractures near the elbow. Logistic regression analysis on casting plus functional bracing was run to determine if age, translation, or the number of days in brace were associated with refracture. The incidence of refracture was compared between groups. Results: A total of 1549 patients were screened and 426 were included in the study [111 casting only (CO), 259 casting plus functional brace <8 wk (CFB <8 wk), 56 casting plus functional brace ≥8 wk (CFB ≥8 wk)]. In comparing the groups, CO was the youngest (4.4 y vs. 6.3 and 8.4 y). The initial translation and angulation of the radius and ulna were significantly greater in the CFB ≥8 weeks group. Regression analyses shows no association between refracture and initial fracture characteristics including age, translation, or the number of days in brace. The CO group had 3 refractures (2.7%), the CFB <8 weeks group had 13 (5%) and the CFB ≥8 weeks group had 1 (1.8%); demonstrating no statistical significance. Conclusion: Extended fracture bracing, following a period of cast immobilization, did not lead to a statistically significant difference in refracture rate. Contrary to previous cases series, the benefit of bracing seems nominal. Larger, prospective studies are needed to better understand targets for treatment. Level of Evidence: This is the first level III retrospective comparison study of its kind.